NATIONAL INSTITUTIONS AND PROTECTION OF HUMAN RIGHTS: ROLE OF NHRC IN THE DEVELOPMENT OF LAW (NATIONAL CAPITAL LAW JOURNAL, 2006)
NA
Keywords: NHRC; Human Rights; Protection; TADA; Fundamental Rights; Constitutional Validity; Custodial Violence; Convention Against Torture; Refugees; International Instruments; Civil Liberties; Child Marriage; Armed Forces Act; Judicial Review; Accountability; Human Dignity; Safeguards